2015
DOI: 10.5455/bcp.20150210030606
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Gender Differences in Substance Use Among Children and Adolescents Admitted to an Addiction Treatment Center in Turkey: Years 2011–2013

Abstract: Trends and gender differences in substance use among children and adolescents admitted to an addiction treatment center in Turkey: years 2011-2013 Objective: In this study we aimed to examine the trends and gender differences in substance use behaviors and treatment seeking patterns of children and adolescents who were admitted to an addiction treatment center in Turkey. Method: Participants were 2718 children and adolescents who had been consecutively admitted to the 'Children and Adolescent Alcohol and Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Often a psychiatric disease accompanies substance use in adolescents. In a public sample study, it was shown that at least one psychiatric disorder accompanied substance addiction in 90% of adolescents under the age of 15; and the most frequent accompanying psychiatric disorders were conduct disorder (72.4%), attention deficit disorder with hyperactivity (63.6%), and depression (52.7%) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often a psychiatric disease accompanies substance use in adolescents. In a public sample study, it was shown that at least one psychiatric disorder accompanied substance addiction in 90% of adolescents under the age of 15; and the most frequent accompanying psychiatric disorders were conduct disorder (72.4%), attention deficit disorder with hyperactivity (63.6%), and depression (52.7%) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, substance use and addiction as an overall worldwide issue have become an important problem for our country as well [ 1 , 2 ]. There are two crucial findings concerning the studies on substance use: there has been a rapid increase in in USA and in our rates of substance use among the adolescents (high school students) country in recent years; and there has been a decrease in tobacco and alcohol use, while the age of first substance use has become younger [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Looking at the trends in opiate usage, we found the highest prevalence in 2014. A study from Turkey, 17 including 2718 youths admitted to an addiction treatment center reported the increased heroin use prevalence through the years in males. 17 Reported data on the prevalence of opiate usage is highly variable in different geographical regions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of psychoactive substance use among the youth, especially students, is a serious health problem that should be closely monitored [20,21]. Studies have shown that the youth are at a high risk of substance use [22][23][24]. Several risk factors are associated with psychoactive substance use among university students [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%